Cleaning the periodicity in discrete- and continuous-time nonlinear dynamical systems - Rech P.C.* (2014)
We investigate periodicity suppression in two-dimensional parameter-spaces of discrete- and continuous-time nonlinear dynamical systems, modeled respectively by a two-dimensional map and a set of three first-order ordinary differential equations. We show for both cases that, by varying the amplitude of an external periodic forcing with a fixed angular frequency, windows of periodicity embedded in a chaotic region may be totally suppressed. © 2014 World Scientific Publishing Company.